New features for performance enhancment of experimental model bubbling fludized bed combustor. (2012)
Fuel flexibility and capacity to burn broad spectrum of fuels at high combustion efficiency with minimum emissions of greenhouse gases are few of the key advantages fluidized bed combustion technology has over other existing combustion technology This report examines the design, development and testing of an experimental model Bubbling fluidized bed combustor. Three unique features to enhance performance of the system were suggested and comprehensively discussed; inert bed's temperature regulating unit, an integrated unit that enable Fluidizing air pre-heating as well as Biomass feeding pipe's cooling and segmentations of the Combustor body into modules /partitioning of these modules into lower and upper section. The results of the test run with Palm kernel shell and Coconut shell show that the system performance is enhanced and that the temperature is well regulated as observed in the thermal distribution. Its is therefore proposed that the present Bubbling Fluidized bed combustor could be beneficial to development of commercial sizes for power generation in Nigeria and Africa sub region.